2022
DOI: 10.1021/acschembio.1c00861
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Synthesis of Natural Parasitic Cysteine Protease Inhibitors: Pentacitidins Are More Potent Falcitidin Analogues

Abstract: Protease inhibitors represent a promising therapeutic option for the treatment of parasitic diseases such as malaria and human African trypanosomiasis. Falcitidin was the first member of a new class of inhibitors of falcipain-2, a cysteine protease of the malaria parasite Plasmodium falciparum. Using a metabolomics dataset of 25 Chitinophaga strains for molecular networking enabled identification of over 30 natural analogues of falcitidin. Based on MS/MS spectra, they vary in their amino acid chain length, seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 61 publications
(117 reference statements)
1
10
0
Order By: Relevance
“…13). 76 It is congruent with the pentapeptide structure, strengthening the degradation hypothesis. The BGC contains a terminal reductase domain probably involved in the formation of the C-terminal aldehyde and alcohol analogs via reductive release.…”
Section: Short Linear Peptidesmentioning
confidence: 56%
See 4 more Smart Citations
“…13). 76 It is congruent with the pentapeptide structure, strengthening the degradation hypothesis. The BGC contains a terminal reductase domain probably involved in the formation of the C-terminal aldehyde and alcohol analogs via reductive release.…”
Section: Short Linear Peptidesmentioning
confidence: 56%
“…NMR spectroscopy revealed that both pentacitidins were puried as diastereomers for the Phe residue. 76 Interestingly, a pentapeptide and its corresponding falcitidin tetrapeptide analog with a C-terminal amidated proline were detected by UHPLC-MS, following the NMR analysis of pure pentacitidins, suggesting that falcitidin-like tetrapeptides are the degradation products of the mature natural productsthe pentacitidins. 76 Further studies are needed to test this hypothesis and elucidate the degradation mechanism.…”
Section: Short Linear Peptidesmentioning
confidence: 99%
See 3 more Smart Citations